On a novel solid lubricant–coated cutting tool: Experimental investigation and finite element simulations. (November 2015) - Kishawy, Hossam A; Reddy, Narala SK; Ghandehariun, Amirmohammad; Abdelmoneam, Hussein M
Developing improved coated cutting tools to achieve a better cutting performance is one of the key factors in enhancing machining productivity. The present article contributes to the development of electrostatic solid lubricant coating technology to produce high-performance coated tools for machining process improvement. Machining tests and finite element analysis were performed to evaluate the proposed novel coating technique. The results obtained from the experiments and simulations demonstrate the effectiveness of the presented technology in reducing the generated heat during machining as well as enhancing wear characteristics of the tool. The results also prove that the developed solid lubricant coating technique will play an important role in sustainable machining.